Effect of Vitamin D deficiency and some hematological parameters in Iraqi female patients with Systemic Lupus Erythematosus - Noori Ali, Ekhlass; Hasan Hussein, Ranya; Taher Mohammed, Sabaa; Ali Ajah, Hamzia (Tikrit Journal of Pure Science, 2024)
Background: Systemic Lupus Erythematosus (SLE) is a chronic inflammatory autoimmune disease that affects multiple organs. Vitamin D deficiency is considered potential environmental factor triggering some autoimmune disorders, including SLE. This study was performed for determination of effect of vitamin D deficiency in SLE infection or disease worsening, and the relationship of ESR, HB, and WBCs with level of vitamin D in SLE disease, in addition to determine which of the previous parameter may describe the disease case of patients. Methods: This study included fifty three (53) SLE female patients and twenty six (26) healthy females were included. White blood count (WBC) and Heamoglobin (Hb) were determined in complete blood count (CBC) device, traditional Westergren method was used for Erythrocyte sedimentation rate (ESR) estimation, vitamin D was measured by using enzyme link immune-sorbent assay (ELISA) Kit. Results: The results showed a significant decrease in the hemoglobin levels in the SLE patients; significant increase was noticed in the ESR of SLE patients and significant increase was noticed in the WBC counts compared to the control group’s samples. A significant decrease in serum levels of vitamin D in patients compared to apparently healthy controls. Conclusions: Photosensitivity to sun in SLE patients contributed in decrease of vitamin D blood-levels. According to the ROC results, each of Hb, WBC, ESR and vitamin D may describe the disease case of patients.